2019
DOI: 10.2174/1381612825666190708214240
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticles: Properties and Applications in Cancer Immunotherapy

Abstract: Background:: Tumours are no longer regarded as isolated masses of aberrantly proliferating epithelial cells. Rather, their properties depend on complex interactions between epithelial cancer cells and the surrounding stromal compartment within the tumour microenvironment. In particular, leukocyte infiltration plays a role in controlling tumour development and is now considered one of the hallmarks of cancer. Thus, in the last few years, immunotherapy has become a promising strategy to fight cancer, as its goal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 203 publications
(279 reference statements)
0
9
0
Order By: Relevance
“…[10] However, again the reliance on passive tropism of cells results in a lack of specificity, presents challenges with respect to the delivery of the concentrations required to elicit significant efficacious responses and therefore risks abscopal toxicity. Equally, although liposomes, [11] dendrimers, [12] and polymeric nanoparticles [13] have demonstrated shielding and cell binding advantages, [14] the ultimate carrier must simultaneously provide active guidance. [6] In this study, we combine the therapeutic activity of the OV (HSV1716) with nanomagnets (magnetosomes, MAG) isolated from specialized magnetotactic bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…[10] However, again the reliance on passive tropism of cells results in a lack of specificity, presents challenges with respect to the delivery of the concentrations required to elicit significant efficacious responses and therefore risks abscopal toxicity. Equally, although liposomes, [11] dendrimers, [12] and polymeric nanoparticles [13] have demonstrated shielding and cell binding advantages, [14] the ultimate carrier must simultaneously provide active guidance. [6] In this study, we combine the therapeutic activity of the OV (HSV1716) with nanomagnets (magnetosomes, MAG) isolated from specialized magnetotactic bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…We have shown that the adoption of a more targeted approach for systemic delivery of OVs can increase their concentration at the target tumor through magnetic targeting ( Howard et al, 2022 ) and cell delivery ( Muthana et al, 2011 ; Iscaro et al, 2022 ) for breast and prostate cancers. Further nano-enabled formulations have shielded OVs from immunosurveillance with or without additional ligands for targeted recognition ( Iscaro et al, 2019 ). Through these strategies, saturating concentrations of virus may be avoided and hence improve tolerability.…”
Section: Discussionmentioning
confidence: 99%
“…Immunotherapy for cancer refers to the treatment of cancer by activating the body's immune system with drugs to attack tumor cells through the body's natural immunity 294,295 receptor T cells), excitatory antibody receptors for costimulation, cancer vaccines, oncolytic viruses, and bisspecific antibodies 296,297 . Nanoparticles are often used to specifically deliver antigens, adjuvants, and therapeutic agents 298,299 . Nanoparticles themselves can also regulate immune microenvironment of tumors [300][301][302][303] .…”
Section: Immunotherapymentioning
confidence: 99%